Pengaruh Model Pembelajaran Example Non Example berbantuan Media Puzzle Bangun Datar Terhadap Kemampuan Pemahaman Konsep Siswa Kelas IV - Lestari, Ester; Rini, Zulmi Roestika (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to determine the effect of non-example learning models assisted by flat puzzle media on students' conceptual understanding of flat shape material. The study used a quantitative experimental type method with a form of nonequivalent control group design. population in this study were fourth grade students at SDN Langensari 02. While for the sample in this study were class IVA and class IVB. Data collection techniques used are test and no-test (observation, questionnaires, and documentation) Data analysis techniques used the normality test, homogeneity test, independent sample t-test, and simple linear regression test. The results of the study show: (1) There are differences in the application of the example non example learning model to the ability to understand the concept of fourth grade students. This is proven by the significant level which shows the sig count value of 0.000 and 0.000 <0.05. (2) there is an influance of the example non example learning mofdel using flat puzzle on improving students’conceptual understanding skills as evidenced by tcount = 5.436 > t table = 2.069 and a significance value of 0.000<0.05 and influencing the concept understanding ability variable by 56,2 %. So that it can be concluded that the example non-example learning model assisted by flat puzzle media affects students’ concept understanding abilities.